Firm life cycle and advisory directors - Habib, A.; Bhuiyan, M.; Hasan, Mostafa (Sage Publications, 2017)
This article investigates whether the presence of advisory directors and monitoring directors varies across firm life cycle stages. We follow a parsimonious life cycle proxy based on the predicted behaviour of operating, investing and financing cash flows across the different life cycle stages that result from firm performance and the allocation of resources. Using an Australian sample, this study shows that compared to mature-stage firms, firms in the introduction, shake-out and decline stages have more advisory directors. With respect to the demand for monitoring directors, we find that compared to mature-stage firms, firms in the introduction, shake-out and decline stages have fewer monitoring directors on the board. We contribute to the literature on boards of directors by documenting that firms choose an optimal board structure based on their economic characteristics.